2007
DOI: 10.1002/mabi.200700056
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Complexes Based on (Quaternized) Poly[(2‐dimethylamino)ethyl methacrylate]: Behavior in Contact with Blood

Abstract: Polyelectrolyte complexes (PECs) between (quaternized) poly[2-(dimethylamino)ethyl methacrylate] (PDMAEMA) and (crosslinked) N-carboxyethylchitosan (CECh) or poly(2-acrylamido-2-methylpropane sodium sulfonate) (PAMPSNa) were prepared and characterized in terms of their stability, equilibrium water content, and surface morphology. The evaluation of the behavior of the studied PECs in contact with blood revealed that the (crosslinked) CECh/(quaternized) PDMAEMA complexes had lost the inherent PDMAEMA cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…These results suggest that PP may be required above a critical level to significantly shorten the lag time for initial thrombin generation and lead to faster platelet activation and adhesion [31]. Alternately, complexes containing different proportions of PP may have different surface charge distributions, which affected electrostatic interaction with plasma proteins and in turn affected platelet binding and subsequent activation [32].…”
Section: Discussionmentioning
confidence: 96%
“…These results suggest that PP may be required above a critical level to significantly shorten the lag time for initial thrombin generation and lead to faster platelet activation and adhesion [31]. Alternately, complexes containing different proportions of PP may have different surface charge distributions, which affected electrostatic interaction with plasma proteins and in turn affected platelet binding and subsequent activation [32].…”
Section: Discussionmentioning
confidence: 96%
“…The permeabilisation of the outer membrane by pDMAEMA appears to remove the barrier for the antibiotic, In order to use pDMAEMA as an antimicrobial coating or treatment, it must be shown to be safe to humans. Reports on the cytotoxicity of pDMAEMA vary depending on the method of administration, quaternisation of the polymer, other polymers attached and size [65][66][67][68] . Moreau et al 65 found that pDMAEMA caused little or no haemolysis to human red blood cells however, when injected intravenously into the tail vein of rats caused death at 5.1 mg/kg but was tolerated at 2.1 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, PAMPSA was shown to act against blood clotting in a similar way to heparin, either alone 15 or incorporated in copolymers. 16 Setoyama et al…”
Section: Introductionmentioning
confidence: 99%